Fuentes del derecho tributario - Chávez Gonzales, Ángel Marco (2022)
Sources of tax law produce introductory vehicles of regulations (Constitution, Treaties, Law, etc.) through a procedure, whose contents introduce articles, paragraphs, subsections, etc. to the legal system as introduced rules. This article begins with the question: What are the sources of law? and What are they for?, to then deal with the relationship between the general system of sources of law and the sources of tax law, next we address the classification of sources of tax law in the Tax Code in self-generating sources of tax regulations and clarifying sources of tax regulations, and finally the case of tax stability agreements is analyzed.